Où étiez-vous le 11 septembre 2001 ? - Jean-François LEGAULT (E-REA)
A handful of dates have imprinted themselves more deeply in the American psyche: the attack on Pearl Harbor, the first step of Neil Armstrong on the moon or the assassination of John F. Kennedy, to name a few. The author H. L. Hix, in his contribution to the anthology September 11, 2001: American Writers Respond, felt the need to define those particular events: « Certain unforgettable events become "where were you when" events because they locate us, alerting us to or reminding us of who we are. [...] We remember where we were physically when these events occurred, because they tell us where we are spiritually. » (Hix, 2002) For him, 9/11 was the cause for a mass introspection. Thus, I propose to outline a subject of study that few have covered before: what are these « where were you when » events and how do they inform us on the particular nature of 9/11? Indeed, it is striking to note how we repeatedly find, in the whole range of the different representations of the terrorist attacks, this deliberate positioning of an individual facing an event of macroscopic scale. For example, in numerous stories or essays, on the margin of the event they relate, the authors provide the readers with the circumstances in which they have learned of the attacks: in addition to representing 9/11, they relate, consciously or not, "their" 9/11. This practice is distinct from the "testimonies" one finds in works like Afterwords: Stories and Reports from 9/11 and Beyond (Editors of Salon, 2002) or Tower Stories: An Oral History of 9/11 (DiMarco, 2007). These generally come from people who were in direct contact with the event. My focus will rather be on the widespread practice among those who witnessed the events through the media (which is to say the vast majority) to tell 9/11 through the mundane details of the everyday life in which they were absorbed when they received the news. Almost inevitably, their personal stories will provide a precise spatial location, as « I was in my car when I heard on the radio » or « I was early at work when I got a call ». In reviewing the different works and cultural manifestations that enable us to conceptualize what really constitutes this practice of the « where were you when », I will address the printed and televised ads for the memorial at Ground Zero whose slogan was « Where were you when it happened? », Alan Jackson’s country song « Where Were You (When the World Stopped Turning) », the Wherewereyou.org website and various occurrences in anthologies of fiction and poetry (Ulrich Beck’s 110 Stories and William Heyen’s September 11, 2001 : American Writers Respond), as well as novels (William Gibson’s Pattern Recognition). I will demonstrate how the « Where were you when » is a particular type of memory, inscribed in a tension between the micro and macroscopic scales of the event, and how it imposes itself in the background of the whole cultural production linked with 9/11.